In vitro antibacterial activity of the cationic proteins of buffalo polymorphonuclear cells - SINGH, V K; MORE, T; SINGH, SHALINI (The Indian Journal of Animal Sciences, 2013)
PMN cells play an important role in protecting host against invading micro-organisms by using O2 dependent and independent microbicidal systems. The later system in buffaloes has been examined by extracting PMN granular proteins and subjecting to GPC-HPLC column which resulted into'4 fractions and their relative antibacterial efficacies against E. coli and S. aureus were examined. Fractions III and IV were more potent than fractions I and II. The incubation of PMN cell granular proteins with E. coli and S. aureus caused greater binding/internalization offractions containing low molecular weight proteins (fractions III and IV) as assessed by GPC-HPLC. The ultrastructure of buffalo PMN cell revealed the presence of subcellular storage granules.